Swim start and performance in 50 m freestyle in different age categories of competitive swimmers - Ivan Matúš; Bibiana Vadašová; Tomáš Eliaš; Wojciech Czarny; Jana Labudová; Luboš Grznár (IP Iermakov S.S., 2024)
Background and Study Aim. In international races, the winners are decided by hundredths of a second, which is why the swim start plays an important role, especially in the sprint disciplines. The aim of the study is to reveal the differences in kinematic parameters of start and performance in the sprint 50 m freestyle discipline based on gender in different age categories of competitive swimmers at international competitions organized in Slovakia. Material and Methods. The sample consisted of 180 females and 189 males who were divided into age categories (K1, K2, K3). SwimPro cameras and Dartgish software were used to monitor kinematic parameters. The parameters monitored were - block time (BT), time (FT) and distance (FD) of flight, time (UWT) and distance (UWD) underwater, time to 15 m (T15), 25 m (T25) and 50 m (T50). Data were tested by Shapiro-Wilk, Kurskal-Wallis ANOVA and Mann-Whitney U test in Statistica 13.5. Results. In the phase above water level, there were greater differences (p<0.01) in females than in males. Inter-sex differences (p<0.01) were evident in FT in K3, K2 and in FD across all categories. In the underwater phase, differences (p<0.01) were evident in both sexes. Inter-sex differences were more evident in UWT (p<0.01) than UWD (p<0.05). There were inter-sex differences (p<0.01) in ST and SD between all categories except K3. At T15, T25 and T50, differences (p<0.01) were most pronounced between K3 and K2, K1 in females and between all categories in males. Inter-sex differences (p<0.01) were also evident across all categories. Conclusions. The study highlighted differences in 50m freestyle start and performance between age groups and gender, so coaches are advised to design training sessions for swimmers separately.